Pelatihan “Classroom English” Bagi Guru Bahasa Inggris SD di Kabupaten Sleman - Yuyun Yulia; Lusi Nurhayati; Emy Nur Rokhani; Bunga Putri Maulia (Universitas Muhammadiyah Mataram, 2026)
Abstract: The aim of this Community Service program was to provide elementary school English teachers with knowledge, skills, and practical experience in the use of classroom English to support effective language teaching. The training involved 24 participants, consisting of 16 public school teachers and 8 private school teachers in Sleman Regency. The program was conducted in three stages: preparation and feedback sessions (held online) and the core workshop (held onsite at the Independent Language Learning Center, Universitas Negeri Yogyakarta). The workshop successfully enhanced teachers’ understanding of the concept and importance of classroom English, as well as their ability to use simple and context-appropriate expressions and instructions in the classroom. Through microteaching simulations, role-play, and group discussions, participants gained not only theoretical insights but also practical experiences directly applicable to their teaching practice. The program is expected to foster long-term impact by encouraging consistent use of English as the medium of instruction as well as providing students on their language acquisition, thereby creating a more communicative classroom environment and supporting students’ English language development from the early stages of formal education.Abstrak: Tujuan dari kegiatan Pengabdian kepada Masyarakat ini adalah untuk memberikan pengetahuan, keterampilan, dan pengalaman praktis kepada guru terkait penggunaan classroom English dalam pengajaran Bahasa Inggris di Sekolah Dasar. Peserta pelatihan berjumlah 24 guru SD, yang terdiri dari 16 guru sekolah negeri dan 8 guru sekolah swasta di Kabupaten Sleman. Kegiatan dilaksanakan dalam tiga tahap, yaitu persiapan dan umpan balik (dilaksanakan secara daring) serta pelaksanaan pelatihan (dilaksanakan secara luring di ruang ILLC Unit Layanan Bahasa Universitas Negeri Yogyakarta). Pelatihan ini berhasil meningkatkan pemahaman guru mengenai konsep dan pentingnya classroom English serta keterampilan praktis dalam menggunakan frasa dan instruksi sederhana yang sesuai dengan konteks pembelajaran di kelas. Melalui simulasi mengajar, role-play, dan diskusi kelompok, guru tidak hanya memperoleh wawasan teoretis tetapi juga pengalaman praktik nyata yang aplikatif. Kegiatan ini memiliki dampak jangka panjang dalam mendorong konsistensi penggunaan bahasa Inggris sebagai bahasa pengantar di kelas, sehingga dapat menciptakan lingkungan belajar bagi peserta didik (language acquition) dan pembelajaran menjadi lebih komunikatif serta mendukung peningkatan kompetensi bahasa Inggris bagi peserta didik jenjang pendidikan dasar.